USING ARTIFICIAL INTELLIGENCE TO ENHANCE ENGLISH LANGUAGE LEARNING - Mamadiyorova Sevara Olimjon's daughter, (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2024)
This article explores the transformative role of Artificial Intelligence (AI) in English language learning, focusing on its ability to provide personalized learning experiences, real-time feedback, pronunciation improvement, and immersive practice. By analyzing the strengths and limitations of AI-powered tools such as chatbots, virtual tutors, speech recognition software, and adaptive learning platforms, the study aims to determine how effectively AI can enhance English language proficiency. The research draws on a combination of quantitative data and qualitative case studies to evaluate the impact of AI in educational settings, providing a comprehensive understanding of the challenges and opportunities in integrating AI into language learning. Ultimately, the findings suggest that AI is a powerful complement to traditional teaching methods, offering individualized and scalable learning experiences that can be fine-tuned to meet the needs of diverse learners.